Economies of Scale and Outsourcing of Agricultural Labor in the Pampa Region (Argentina) - Lombardo, Patricia Beatriz (2018)
In the last decades in Argentina, especially in the Pampa region, there has been a significant decrease of agricultural farms and permanent workers, as well as an increase in the outsourcing of agricultural labor. In this context, contractors offering agricultural machinery services have become a key piece in the increase of production efficiency due to their ability to respond on a flexible and agile manner to technical changes and labor organization. Those demanding these services constitute a heterogeneous universe both in production, as well as in composition and technological requirements, which affects the way they relate with contractors. Significantly important among these groups are the “sowing pools”, which are enterprises based on the generation of economies of scale that operate large areas of land and prefer renting machinery. The general objective of this paper was to analyze the types of relationships between these enterprises and machinery contractors. A qualitative approach was used, and information was collected through semi-structured interviews.